Quality of life in patients with long-term Ventricular Assist Devices (Research, Society and Development, 2021)
For advanced heart failure refractory to clinical therapy, heart transplantation is the gold standard of treatment. However, due to the difficulty of available donors and the capture of viable organs, Ventricular Assistance Devices (VAD) emerged, offering mechanical circulatory support as an alternative method for these patients, aiming to improve quality of life and survival rate. The study aimed to identify, in the scientific literature, the perspective on the quality of life of patients who use VAD and its impacts, in studies published nationally and internationally. This is an integrative literature review of narrative analysis, carried out in national and international databases using the PICO strategy. The search was carried out with the help of a professional librarian and the selection was made in pairs by two researchers, obtaining a final sample of 21 studies. There are positive and negative factors that must be considered with the history, clinical condition, therapy, motivation, fear, coping, emotional and social support, among others. Patients using VAD show improvement in symptoms, reduce clinical decompensation resulting from heart failure and, consequently, improve quality of life.